Using Game Theory For Allocation Of Transmission Losses Between The Investors in Deregulated Electrical Power System - Massoud Sabyh; Tammam Haydar; Rama Salloum (Tishreen University, 2020)
Liberalization and deregulation in the electricity sector leads to competition in the energy market. Since the main part of electricity pricing is the fair and equitable allocation of system losses, allocation of transmission loss has become a contention issue among the electricity producers and consumers. It is difficult to find a formula for resolving the transmission loss allocation problem because of the fact that transmission losses are not linear in relation to loads. Different methods are used to allocate transport losses, but most of these methods lack economic fundamentals and also include complex calculations and time-consuming calculations. The concept of Shapley Value adopted from cooperative game theory is used to deal with the fairness of the allocation of loss. Where this method takes into consideration the configuration of the network and the relationships between the players and there is no need to specify the sharing factors of losses to be allocated to the supply side and demand side. The results are tested using the network IEEE 14 bus system. أدى تحرير قطاع الكهرباء إلى وجود منافسة في سوق الطاقة تقتضي التوزيع العادل والمنصف لضياعات النظام. ولأن الضياعات في شبكات النقل ليست تابعاً خطياً للأحمال كان من الصعب إيجاد صيغ (بنى) رياضية بسيطة لتوزيعها بين المستثمرين وبين المستهلكين المستجرين للطاقة من مجموعات توليد مستثمر ما. يتم استخدام طرق مختلفة لتحديد ضياعات النقل، ولكن معظم هذه الطرق تفتقر الى أسس اقتصادية فنية وتشمل أيضاً عمليات رياضية معقدة وحسابات مستهلكة للوقت. في هذا السياق يأتي استخدام نظرية اللعبة (الشكل التعاوني) من أجل توزيع عادل لهذه الضياعات. يستند الحساب باستخدام هذه النظرية إلى تركيب الشبكة وعلاقات اللاعبين بعضهم مع بعض من دون الحاجة لعوامل إضافية كعوامل المشاركة بالضياع للمولدات والأحمال. تختبر النتائج باستخدام شبكة 14 قضيب تجميع IEEE 14 bus system.